2021
DOI: 10.1101/2021.12.07.471534
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decoupling growth and production by removing the origin of replication from a bacterial chromosome

Abstract: Efficient production of biochemicals and proteins in cell factories frequently benefits from a two-stage bioprocess in which growth and production phases are decoupled. Here we describe a novel growth switch based on the permanent removal of the origin of replication (oriC) from the Escherichia coli chromosome. Without oriC, cells cannot initiate a new round of replication and they stop growing while their metabolism remains active. Our system relies on a serine recombinase from bacteriophage phiC31 whose expr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Enhanced translation upon replication arrest is a possible mechanism to increase protein and metabolite production and has been studied in E. coli (8, 9, 28). To observe whether the levels of translation-related proteins were increased upon replication arrest in B. subtilis , we made individual profile plots of translation-related proteins as a function of the z-score (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Enhanced translation upon replication arrest is a possible mechanism to increase protein and metabolite production and has been studied in E. coli (8, 9, 28). To observe whether the levels of translation-related proteins were increased upon replication arrest in B. subtilis , we made individual profile plots of translation-related proteins as a function of the z-score (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in several bacteria have suggested that protein synthesis continues during growth arrest and that maintaining functional translation machinery may be required for their viability (1012, 38). Additionally, several studies in E. coli demonstrated enhanced protein and biochemical production of proteins and metabolites during replication arrest (8, 9, 28). We further confirmed that non-replicating cells maintained a higher rate of protein expression than WT cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation